2013
DOI: 10.1108/so-04-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Cloud sourcing and innovation: slow train coming?

Abstract: Purpose: Although cloud computing has been heralded as driving the innovation agenda, there is growing evidence that cloud is actually a "slow train coming". The purpose of this paper is to seek to understand the factors that drive and inhibit the adoption of cloud particularly in relation to its use for innovative practices.Design/methodology/approach: The paper draws on a composite research base including two detailed surveys and interviews with 56 participants in the cloud supply chain undertaken between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 25 publications
0
46
0
1
Order By: Relevance
“…Tornatzky (2005) suggested that complex technologies could not be adopted successfully and thereby it could not bring the expected efficiency to the organization. Also, complexity factors expected to influence Cloud adoption decisions negatively, and people may not have confidence in the technology because it is relatively new to them (Hsin-Pin et al 2014, Willcocks 2013.…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tornatzky (2005) suggested that complex technologies could not be adopted successfully and thereby it could not bring the expected efficiency to the organization. Also, complexity factors expected to influence Cloud adoption decisions negatively, and people may not have confidence in the technology because it is relatively new to them (Hsin-Pin et al 2014, Willcocks 2013.…”
Section: Complexitymentioning
confidence: 99%
“…Raza et al (2015) explained that controversial view of the fear of job losses in the minds of the workforce is one of the major factors that have contributed slow growth of Cloud computing. Willcocks et al (2013) believes that the adoption of Cloud technology beyond its IT operational benefits could be problematic and slow the adoption, and infrastructure failures could have contributed negatively to rethink about the decision to adopt this technology.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of benefits that CC can offer to firms has been extensively described in previous literature [2,4,12,13,15,22,24,31,32]. These benefits include reduction of the cost and improvement of the quality of the ICT support of firm's processes and activities, conversion of ICT capital investments to operating costs, ubiquitous access to ICT infra-structure using various kinds of devices (e.g.…”
Section: Cloud Computing Benefitsmentioning
confidence: 99%
“…ICT processes, roles, etc.) [27,31,32]; since the existing ICT skills and internal organization are currently aligned with the 'on-premises' paradigm, they have to be changed and adapted to the needs of the new CC paradigm, in order to exploit the full potential of it, and gain significant benefits.…”
Section: Cloud Computing Adaptationmentioning
confidence: 99%
See 1 more Smart Citation